Technical implementation of the semantic enhancements applied to Reis et al. (2008) Impact of environment and social gradient on Leptospira infection in urban slums. PLoS Neglected Tropical Diseases 2(4): e228 - Shotton, D; Portwin, K (Image Bioinformatics Research Group, Department of Zoology, 2009)
Semantic enhancements were made by David Shotton, Katie Portwin, Graham Klyne and Alistair Miles, Image Bioinformatics Research Group, Department of Zoology, University of Oxford to the above-cited PLoS Neglected Tropical Diseases (PLoS NTD) article by Reis et al. (2008). The semantically enhanced version of that article was published on 3 September 2008 at doi:10.1371/journal.pntd.0000228.x001, and the paper by Shotton et al. (2009) describes the full range of semantic enhancement applied to that Reis et al. (2008) article. This document provides a technical description of how those semantic enhancements were implemented. A separate document (Portwin and Shotton, 2009; doi:10.1371/journal.pntd.0000228.x010) describes the heuristics we applied when deciding which textual terms were to be assigned to the semantic classes highlighted in the text of the enhanced version of the Reis et al. (2008) article.